Підходи до залучення та інформування клієнтів турфірми у соціальних мережах - Бекеш, Юлія; Федушко, Соломія (Видавництво Львівської політехніки, 2014)
This article analyzes the methods of forming a travel company customer base with the help of social networks. These methods are made to involve users of the social network "VKontakte" for positioning of the service of the travel company "New Europe" on the Internet. The methods of applying the maintenance activities and interests of users are also used.
Keywords: соціальні мережі; туристична фірма; тематична група; клієнтська база; комунікація; статистика